2021
DOI: 10.3390/insects12020159
|View full text |Cite
|
Sign up to set email alerts
|

Operational Parameters for the Aerial Release of Sterile Codling Moths Using an Uncrewed Aircraft System

Abstract: The codling moth is a serious pest of apples in most regions of the world where this fruit is produced. The sterile insect technique is one strategy used to control this pest and is employed as part of an area-wide integrated pest management program for the codling moth in British Columbia, Canada. Modified fixed wing aircraft are the most common method for the release of sterile insects in large area-wide pest management programs. However, aerial release with a full-size aircraft can be prohibitively expensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(101 reference statements)
0
4
0
Order By: Relevance
“…High amounts of paved surfaces in urban environments may require adjustments to the release strategy to make releases earlier in the day or in the evenings after the heat of the day, which may improve moth performance and survivorship. Aerial release over gardens and trees may also be beneficial compared to ground release onto paved areas and may also increase moth survivorship, along with improved dispersion of moths, as seen in some other systems [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…High amounts of paved surfaces in urban environments may require adjustments to the release strategy to make releases earlier in the day or in the evenings after the heat of the day, which may improve moth performance and survivorship. Aerial release over gardens and trees may also be beneficial compared to ground release onto paved areas and may also increase moth survivorship, along with improved dispersion of moths, as seen in some other systems [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that these populations need to be reduced by SIT applications in the frame of an AW-IPM suppression program. Esch and colleagues (2021) [ 19 ] showed that sterile codling moths can be successfully released by small uncrewed aircraft systems (UASs). The data presented clearly indicate that UAS-based releases achieved higher recapture rates as compared with ground releases and are much cheaper to operate than the commonly used fixed wing aircraft for the release of sterile moths.…”
Section: Lepidopteramentioning
confidence: 99%
“…My results substantiate the importance of distributing the sterile ticks to all parts of the control area: a good deal more time and/or sterile ticks are required for even slightly less than thorough release. Thorough distribution certainly necessitates aerial release [80], which unfortunately is often a sizable portion of SIT program expense (when used), in some cases increasing costs by as much as 70% [83,84]. This is much lower than the increase in release needed for the "poor" distribution, but is similar to the change in time required.…”
Section: Sterile Tick Distributionmentioning
confidence: 99%